2015
DOI: 10.1016/j.hrtlng.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to evidence-based secondary prevention pharmacotherapy in patients after an acute coronary syndrome: A systematic review

Abstract: Adherence to secondary prevention pharmacotherapy was suboptimal in patients after hospital discharge for an ACS. Risk factors associated with non-adherence were examined in a limited number of studies, and the associations varied between these investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 50 publications
2
43
1
4
Order By: Relevance
“…To the best of our knowledge, there are no studies assessing medication adherence after hospitalization for CHD using GBTM. Traditional studies assessing adherence to secondary prevention pharmacotherapy after an ACS showed suboptimal figures (ranging from 54% to 86% at one year) [17], although such figures are not directly comparable to those of the present study, as they do not provide information on adherence behaviors over time.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…To the best of our knowledge, there are no studies assessing medication adherence after hospitalization for CHD using GBTM. Traditional studies assessing adherence to secondary prevention pharmacotherapy after an ACS showed suboptimal figures (ranging from 54% to 86% at one year) [17], although such figures are not directly comparable to those of the present study, as they do not provide information on adherence behaviors over time.…”
Section: Discussioncontrasting
confidence: 95%
“…Coronary heart disease (CHD) provides an opportunity to explore the potential of these alternatives. In spite of great efforts from the scientific community and professional societies through clear guideline recommendations and quality of care policies based on solid evidence, underprescribing and low adherence to evidence-based therapies remain a significant problem in the management of patients who have suffered hospitalization for CHD [4,17], either because physicians fail to prescribe these medications and/or because patients fail to obtain and/or consume them.…”
Section: Introductionmentioning
confidence: 99%
“…Our results were consistent with the finding of other registries in Switzerland with a general high rate of prescription of recommended drugs [14]. Compared to registries from other countries, we found a better optimal prescription rate at discharge and at 1 year [20,21]. However, the results of registries are highly dependent on the method used to assess optimal drug prescription.…”
Section: Discussionsupporting
confidence: 90%
“…The reasons for patient non‐adherence to medications are complex. Some studies have highlighted the importance of patient‐related factors such as poor motivation, forgetfulness, co‐existing conditions, socio‐economic status, lack of education about the therapies, complicated polypharmacy regimens and depression, whereas others have identified the treating physician as playing a major role in the patient's decision to stop treatment . The purpose of this study was to identify the relative importance of clinical and treatment factors as predictors of patient adherence to secondary prevention medications at 6 months following an ACS, and thereby define the most efficient strategies to optimise adherence in this high‐risk population.…”
Section: Introductionmentioning
confidence: 99%